An Alternative Approach for the Interpretation of Data from Three-Point Bending of Long Bones - KOURKOULIS, Stavros K.; KOUVAKA, Artemis; ANDRIAKOPOULOU, Chara; DONTAS, Ismene (Engineering Transactions, 2016)
An alternative approach for elaborating the raw data obtained from three-point bending tests of long bones of Wistar rats is described. The aim of the study is to provide mechanical properties of the bone tissue which are independent of the bone geometric characteristics. The study is carried out experimentally ex-vivo. It is indicated that ignoring the actual shape of the bone critical cross-section (i.e., the section where a fracture occurs) and the inclination of the loading axis with respect to the principal centroidal axes of the critical section may lead to erroneous results concerning the strength of the tissue.